High Incidence of Lysogeny in the Oxygen Minimum Zones of the Arabian Sea (Southwest Coast of India) - Ammini Parvathi; Vijayan Jasna; Sreekumar Aparna; Angia Sriram Pradeep Ram; Vijaya Krishna Aswathy; Kizhakkeppat K. Balachandran; Kallungal Ravunnikutty Muraleedharan; Dayana Mathew; Telesphore Sime-Ngando (Viruses, 2018)
Though microbial processes in the oxygen minimum zones (OMZs) of the Arabian Sea (AS) are well documented, prokaryote-virus interactions are less known. The present study was carried out to determine the potential physico-chemical factors influencing viral abundances and their life strategies (lytic and lysogenic) along the vertical gradient in the OMZ of the AS (southwest coast of India). Water samples were collected during the southwest monsoon (SWM) season in two consecutive years (2015 and 2016) from different depths, namely, the surface layer, secondary chlorophyll a maxima (~30⁻40 m), oxycline (~70⁻80 m), and hypoxic/suboxic layers (~200⁻350 m). The high viral abundances observed in oxygenated surface waters (mean ± SD = 6.1 ± 3.4 × 106 viral-like particles (VLPs) mL−1), drastically decreased with depth in the oxycline region (1.2 ± 0.5 × 106 VLPs mL−1) and hypoxic/suboxic waters (0.3 ± 0.3 × 106 VLPs mL−1). Virus to prokaryote ratio fluctuated in the mixed layer (~10) and declined significantly (p < 0.001) to 1 in the hypoxic layer. Viral production (VP) and frequency of virus infected cells (FIC) were maximum in the surface and minimum in the oxycline layer, whereas the viral lysis was undetectable in the suboxic/hypoxic layer. The detection of a high percentage of lysogeny in suboxic (48%) and oxycline zones (9⁻24%), accompanied by undetectable rates of lytic viral infection support the hypothesis that lysogeny may represent the major survival strategy for viruses in unproductive or harsh nutrient/host conditions in deoxygenated waters.